Die Lebenszeugnisse Oswalds von Wolkenstein, Band 1 Band 1: 1382-1419, Nr. 1-92, Edition und Kommentar - Kranich-Hofbauer, Karin (1999)
The first of five volumes presents the younger son of Tyrolean country gentry as a squire bustling striving for social advancement. After unsteady years as a noble warrior, crusader and expert for public administration with the Bishop of Brixen, with his admittance to the Service of King Sigmund of Luxemburg he achieves a special role between the sovereign of the Holy Roman Empire and the Tyrolean nobility which rebelled against his Austrian Duke Friedrich IV.